Smoking cessation behaviors three months following acute insular damage from stroke. (December 2015) - Abdolahi, Amir; Williams, Geoffrey C.; Benesch, Curtis G.; Wang, Henry Z.; Spitzer, Eric M.; Scott, Bryan E.; Block, Robert C.; van Wijngaarden, Edwin
Abstract: Background: Recent evidence suggests that the insular cortex may play an important role in cognitive and emotional processes that facilitate drug use but it is unclear whether changes to the insula would result in sustained abstinence. To better understand the role of the insula in maintaining abstinence, we examined quitting patterns in smokers with acute damage to their insula relative to other regions. Design: Prospective cohort study with 3 month follow-up, beginning June 2013 and ending May 2014. Setting: Three acute care hospitals in Rochester, NY. Participants: One-hundred-fifty-six current smokers hospitalized for acute ischemic stroke; 38 with insular infarctions and 118 with non-insular infarctions, assessed by 3 neuroradiologists. Measurements: Self-reported smoking status (seven-day point prevalence and continuous abstinence), complete abstinence from any nicotine product, and disruption of smoking addiction (defined by criteria on smoking status, difficulty of quitting, and urge) were assessed at three months post-stroke. Time to relapse (in days) after discharge was also assessed. Results: Insular damage was associated with increased odds of three-month continuous abstinence (OR = 3.71, 95% CI: 1.59, 8.65) and complete cessation from any nicotine product (OR = 2.72, 95% CI: 1.19, 6.22). Average time to relapse was longer in the insular-damaged group (17.50 days, SD = 19.82) relative to non-insular damage (10.42 days, SD = 18.49). Among quitters, insular damage was also associated with higher relative odds of experiencing a disruption of addiction compared to non-insular damage (adjusted OR = 5.60, 95% CI: 1.52, 20.56). Conclusions: These findings support the potential role of the insular cortex in maintaining smoking and nicotine abstinence. Further research is needed to establish whether the insula may be a novel target for smoking cessation interventions. Highlights: Insular damage is associated with increased odds of 3-month continuous abstinence. Insular damage increases the odds of complete cessation for any nicotine product. Time to smoking relapse is higher on average in those with insular lesions. Those abstinent by 3 months with insular damage did not smoke at all post-discharge. The insula may be a target for long-term smoking cessation therapies.